2016
DOI: 10.1186/s12889-016-3626-4
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional associations between psychosocial well-being and body mass index in European children: longitudinal findings from the IDEFICS study

Abstract: BackgroundThe negative impact of childhood overweight on psychosocial well-being has been demonstrated in a number of studies. There is also evidence that psychosocial well-being may influence future overweight. We examined the bidirectional association between childhood overweight and psychosocial well-being in children from a large European cohort.The dual aim was to investigate the chronology of associations between overweight and psychosocial health indicators and the extent to which these associations may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
(46 reference statements)
0
20
0
4
Order By: Relevance
“…In fact, a scientific paper that investigated the associations between socioeconomic disadvantages and psychosocial problems found that having parents with a lack of a social network was the strongest determining factor to predict children's internalizing and psychosocial problems ( 46 ). The negative impact of childhood overweight on psychosocial well-being has been demonstrated in many studies, but the association between overweight and psychosocial well-being may be bidirectional because there is also evidence that psychosocial well-being may influence future overweight ( 49 ).…”
Section: Classic Ses and Social Disadvantages And Their Consequences mentioning
confidence: 99%
“…In fact, a scientific paper that investigated the associations between socioeconomic disadvantages and psychosocial problems found that having parents with a lack of a social network was the strongest determining factor to predict children's internalizing and psychosocial problems ( 46 ). The negative impact of childhood overweight on psychosocial well-being has been demonstrated in many studies, but the association between overweight and psychosocial well-being may be bidirectional because there is also evidence that psychosocial well-being may influence future overweight ( 49 ).…”
Section: Classic Ses and Social Disadvantages And Their Consequences mentioning
confidence: 99%
“…Similar studies from Iran indicate lower HRQol scores in obese children, compared to their over-or normal-weight counterparts [13,14] which can be observed in a gender-speci c pattern [15]. On the other hand results of a longitudinal study conducted on European children revealed bidirectional associations between childhood overweight and psychosocial well-being [16]; ndings consistent with previous data indicate that mental health problems and poor psychosocial well-being during childhood increased the risk of future obesity [17][18][19]. Hence, investigating the association between weight status and HRQoL in children and adolescents, considering the main factors that can affect their weight and HRQoL simultaneously, would provide much needed data on this very important relationship.…”
Section: Introductionmentioning
confidence: 74%
“…In accordance with the SDQ manual [ 28 ] the emotional and peer problem scores were divided into: ‘inconspicuous’, ‘borderline’ and ‘abnormal’. Thereafter, a dichotomized variable was created, as previously done by Hunsberger et al [ 12 ], consisting of poor well-being (including both ‘borderline’ and ‘abnormal’ groups) versus the remaining children with no detectable (‘inconspicuous’) poor wellbeing.…”
Section: Methodsmentioning
confidence: 99%
“…However, one has to acknowledge the possible effect of children’s weight status on the association between diet and psychosocial well-being [ 6 , 11 ]. For example, recent results from the IDEFICS (Identification and Prevention of Dietary- and Lifestyle-Induced Health Effects in Children and Infants study) suggests that childhood overweight increases the risk of poor health-related quality of life while poor well-being increases the risk of developing overweight [ 12 ].…”
Section: Introductionmentioning
confidence: 99%